Nanoscale Pore Structure Characterization and Permeability of Mudrocks and Fine-Grained Sandstones in Coal Reservoirs by Scanning Electron Microscopy, Mercury Intrusion Porosimetry, and Low-Field Nuclear Magnetic Resonance - Na Zhang; Fangfang Zhao; Pingye Guo; Jiabin Li; Weili Gong; Zhibiao Guo; Xiaoming Sun (Geofluids)
Porosity and permeability of two typical sedimentary rocks in coal bearing strata of underground coal mines in China, i.e., mudrocks and fine-grained sandstones, were comprehensively investigated by multiple experimental methods. Measured porosity averages of the helium gas porosity (φg), MIP porosity (φMIP), water porosity (φw), and NMR porosity (φNMR) of the twelve investigated rock samples range from 1.78 to 16.50% and the measured gas permeabilities (Kg) range from 0.0003 to 2.4133 mD. Meanwhile, pore types, pore morphologies, and pore size distributions (PSD) were determined by focused ion beam scanning electron microscopy (FIB-SEM), mercury intrusion porosimetry (MIP), and low-field nuclear magnetic resonance (NMR). FIB-SEM image analyses showed that the mineral matrix pores including interparticle (interP) and intraparticle (intraP) pores with varied morphologies are the dominant pore types of the investigated rock samples while very few organic matter (OM) pores were observed. Results of the MIP and the full water-saturated NMR measurements showed that the PSD curves of the mudrock samples mostly present a unimodal pattern and nanopores with pore diameter less than 0.1 μm are their predominant pore type, while the PSD curves of the fine-grained sandstone samples are featured by a bimodal distribution. Furthermore, comparison of the full water-saturated and irreducible-water-saturated NMR measurements indicated that pores in the mudrocks are solely adsorption pores (normally pore size < 0.1 μm) whereas apart from a fraction of adsorption pores, a large part of the pores in the sandstone sample with relatively high porosity are seepage pores (normally pore size > 0.1 μm). Moreover, the PSD curves of NMR quantitatively converted from the NMR T2 spectra by T2Pc and weighted arithmetic mean (WAM) methods are in good agreement with the PSD curves of MIP. Finally, the applicability of three classic permeability estimation models based on MIP and NMR data to the investigated rock samples was evaluated.